2000
DOI: 10.1016/s0033-3506(00)00368-1
|View full text |Cite
|
Sign up to set email alerts
|

Day care centres as an institution for health promotion among needy children an analytical study in São Paulo, Brazil

Abstract: The nutritional status of children attended in the day care centers was better than children of the same community receiving other types of daily care (OR=0.48; CI 95%=0.36-0.65;P>0.0001). The improvement was related to more than 1 year of enrollment in the day care (OR=0.74; CI 95%=0.57-0.96;P=0.02).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 0 publications
0
11
0
8
Order By: Relevance
“…A distribuição geográfica dos locais onde foram realizados os estudos mostra maior concentração no estado de São Paulo (14 estudos) 10,12,14,17,19,21,22,24,25,27,33 . Nas macrorregiões Nordeste 15,18,26,28 e Sul 16,20 , foram realizados quatro e dois estudos, respectivamente, enquanto no Norte 32 apenas um estudo foi realizado.…”
Section: R E S U L T a D O Sunclassified
See 3 more Smart Citations
“…A distribuição geográfica dos locais onde foram realizados os estudos mostra maior concentração no estado de São Paulo (14 estudos) 10,12,14,17,19,21,22,24,25,27,33 . Nas macrorregiões Nordeste 15,18,26,28 e Sul 16,20 , foram realizados quatro e dois estudos, respectivamente, enquanto no Norte 32 apenas um estudo foi realizado.…”
Section: R E S U L T a D O Sunclassified
“…Análises múltiplas que controlaram variáveis de confundimento foram conduzidas em nove dos estudos revisados [15][16][17][19][20][21][22]24,25 , e todos esses estudos apresentaram qualidade metodológica alta. Os resultados apontaram a idade da criança (4 estudos) 16,17,19,21 , o peso ao nascer (3 estudos) 16,17,24 , o número de irmãos (2 estudos) 19,21 , a renda familiar 22,25 , a escolaridade da mãe 22,25 e o tempo de frequência à creche (2 estudos) 24,25 como as variáveis associadas de maior recorrência. As condições de risco relacionadas ao número de irmãos 19,21 , à renda familiar 22,25 e à escolaridade materna 22,25 associaram-se ao déficit de estatura da criança.…”
Section: R E S U L T a D O Sunclassified
See 2 more Smart Citations
“…Longitudinal studies in Thailand and Colombia showed no difference in nutritional status between DCC attendees and non-attendees [24,25]. A cross-sectional study in Brazil reported better nutritional status among children attending municipal DCCs than non-attendees [26]. A cross-sectional study in Nepal found favourable effects among attendees of a private DCC, but no effects among those of a municipal DCC [27].…”
Section: Introductionmentioning
confidence: 99%